A requirement for Gch1 and tetrahydrobiopterin in embryonic development. - Douglas, G; Hale, AB; Crabtree, M; Ryan, B; Hansler, A; Watschinger, K; Gross, S; Lygate, C; Alp, N; Channon, K (Elsevier, 2015)
INTRODUCTION: GTP cyclohydrolase I (GTPCH) catalyses the first and rate-limiting reaction in the synthesis of the enzymatic cofactor, tetrahydrobiopterin (BH4). Loss of function mutations in the GCH1 gene lead to congenital neurological diseases such as DOPA-responsive dystonia and hyperphenylalaninemia. However, little is known about how GTPCH and BH4 affects embryonic development in utero, and in particular whether metabolic replacement or supplementation in pregnancy is sufficient to rescue genetic GTPCH deficiency in the developing embryo. METHODS AND RESULTS: Gch1 deficient mice were generated by the insertion of loxP sites flanking exons 2-3 of the Gch1 gene. Gch1(fl/fl) mice were bred with Sox2cre mice to generate mice with global Gch1 deficiency. Genetic ablation of Gch1 caused embryonic lethality by E13.5. Despite loss of Gch1 mRNA and GTPCH enzymatic activity, whole embryo BH4 levels were maintained until E11.5, indicating sufficient maternal transfer of BH4 to reach this stage of development. After E11.5, Gch1(-/-) embryos were deficient in BH4, but an unbiased metabolomic screen indicated that the lethality was not due to a gross disturbance in metabolic profile. Embryonic lethality in Gch1(-/-) embryos was not caused by structural abnormalities, but was associated with significant bradycardia at E11.5. Embryonic lethality was not rescued by maternal supplementation of BH4, but was partially rescued, up to E15.5, by maternal supplementation of BH4 and l-DOPA. CONCLUSION: These findings demonstrate a requirement for Gch1 in embryonic development and have important implications for the understanding of pathogenesis and treatment of genetic BH4 deficiencies, as well as the identification of new potential roles for BH4.